2005
DOI: 10.1081/jdi-200065304
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Membranous Nephropathy - One Center Experience

Abstract: A thorough and repeated exclusion of secondary forms of MN has significant prognostic and therapeutic implications, especially in drug-induced and autoimmune MN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
1
19
0
3
Order By: Relevance
“…This result is in accordance with the findings reported by other authors. 5,8 These studies have also shown that the histological type of cancer and proteinuria may have an important role in activate circulating tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This result is in accordance with the findings reported by other authors. 5,8 These studies have also shown that the histological type of cancer and proteinuria may have an important role in activate circulating tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be related to different pathogenic mechanisms. Rihova,5 reported that malignant tumors associated MGN, might be caused by the production of antibodies against tumor cells deposition immune complexes and glomerular deposits. In the same way, Lefaucheur,8 hypothesized that tumorrelated glomerular injury might be related to the inflammatory cells evoked by the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations